(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This study analyzes the impact of climate change on Uzbekistan’s agriculture, using observational data (1960–2023) and modeled projections. Uzbekistan has experienced a mean temperature increase of +1.2 °C since 1991, with declining precipitation and higher drought frequency Under scenarios, crop yields could decline by 25–63% by the 2050s. Findings highlight significant risks to cotton, wheat, and horticulture, especially in water-stressed regions like Karakalpakstan and Khorezm. Key adaptation strategies include water-saving irrigation, climate-resilient crops, and digital monitoring. Policy engagement and institutional support will be critical for sustainable agriculture and food security.